Editorial - Ferrari, Lea; Kukytė, Monika; Katsarov, Johannes W. (Newsletter, 2014)
The creation of a newsletter has been under discussion for a quite a while already in the NICE network. Since our network was founded in 2009, the interest in our efforts has continually grown among professionals, policy-makers and academics dealing with career guidance and counselling - in Europe and worldwide.